ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK PADA PT. WAHYU PERDANA PERSADA DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Ricki, Ricki; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2019)
PT. Wahyu Perdana Persada is one of company which has been located in Jambi where selecting bestemployment still be selected subjective by owner desire. So always get problem like social jealousybetween employment and decrease performance of employment. Because of that, this research havepurpose to give solution to that happening problems with offer a prototype of decision support system ofselecting best employees with using PHP programming language and MySQL database where writermake development prototype system and using model approach system unified modeling language withuse case diagram, activity diagram, class diagram and flowchart diagram. New system make some outputlike show employees data, admin data, assessment criteria data, employees assessment data, and result ofreckoning select best employees with simple additive weighting method (SAW).